Winter‐mixing preconditioning of the spring phytoplankton bloom in the Bay of Biscay. (20th December 2017) - González‐Gil, Ricardo; González Taboada, Fernando; Cáceres, Carlos; Largier, John L.; Anadón, Ricardo
Abstract: The spring phytoplankton bloom plays a key role in the dynamics of temperate and polar seas. Nevertheless, the mechanisms and processes behind these blooms remain a subject of considerable debate. We analyzed the influence of deep mixing during winter on the spring phytoplankton bloom in the Cantabrian Sea (southern Bay of Biscay). To this end, we combined long‐term physical and biogeochemical in situ data (1993–2012) and satellite observations (1997–2012). Deeper winter mixing led to higher nitrate and chlorophyll concentrations through the water column during the spring bloom. However, this effect was modified by short‐term variability in near‐surface stratification in spring. Winter‐mixing preconditioning also influenced different spring bloom metrics: deeper and later mixing in winter was followed by later blooms with a larger peak. In these enhanced blooms, nitrate was taken up at faster rates, indicating higher rates of phytoplankton production. Winters with weaker mixing (that led to weaker spring blooms) were associated with warmer surface temperatures. This relationship suggests that the multi‐decadal trend toward warmer surface temperatures in the Bay of Biscay may promote a decrease in the magnitude of the spring bloom, which could impact upper trophic levels and also deep carbon export in the future.